Earning Management as a Mediator of the Influence of Good Corporate Governance on Company Value in Each Company Life Cycle - Setiawan, Putu Ery; Wiagustini, Ni Luh Putu; Yadnyana, I Ketut; Baskara, I Gede Kajeng (Jurnal Ilmiah Akuntansi dan Bisnis, 2024)
This research utilizes the capital structure theory to analyze how debt covenants, corporate governance, and firm value interact, focusing on the mediating role of earnings management across different company life stages. It examines manufacturing firms on the Indonesia Stock Exchange from 2018 to 2022, using a purposive sample of 66 companies. The study employs descriptive and inferential statistical analyses to test the hypothesized relationships, revealing that effective corporate governance significantly enhances firm value, especially during maturity. Earnings management is pivotal in the growth phase, mediating the governance-firm value relationship. This work underscores the importance of adapting governance practices to a company's life cycle stage, offering insights for executives to make financial decisions that improve firm value. It also provides empirical support for agency theory, showing how tailored governance practices can influence firm performance and value. Keywords : earnings management, good corporate governance, company value, company life cycle